Off-the-shelf digital tools as a resource to nurture the commons - Mela Bettega; Raul Masu; Nicolai Brodersen Hansen; Maurizio Teli (My University, 2022)
Commons and commoning are of increasing interest to the PD community. We argue that off-the-shelf digital commons can be used in the context of PD to support groups in their commoning practices. This approach presents some advantages: it allows focusing resources on participation rather than software development and it fosters sustainability of results when researchers leave. But how do we understand whether an off-the-shelf tool can be considered a commons or not? Where do we find digital commons? How do we select them? In this paper, we will try to answer these questions by proposing theoretical considerations and practical criteria based on the reflexive account of a case study in Europe.
Keywords: Nature versus nurture; Reflexivity; peer production; Open Source Software Innovations